Policiamento transnacional: uma análise da cooperação entre Brasil e Bolívia no combate ao tráfico de drogas (2008-2012) - Castro, Helena Salim de (2017)
International drug trafficking is one of the main security threats to the countries of South America, especially Brazil and Bolivia. The Andean country is the third largest cocaine producer in the world and the Brazilian territory is one of the main transit routes for drugs sent to Europe, as well as being considered the main consumer market for Bolivian cocaine.In the literature there are still few studies that deal with the relationship between the two countries concerningthis issue.So, the main objective of this research was to analyze the type of cooperation developed between Brazil and Bolivia for policing the fight against drug trafficking.Our period of analysis has been since November 2008, when, after decades of US influence and interference in Bolivia's anti-drug policies, the Drug Enforcement Administration (DEA) was expelled from Bolivian territory, which led to an approximation between the Brazilian and Bolivian governments, until the end of January 2012, when a trilateral agreement was signed between Bolivia, Brazil and the United States. This agreementmarked the return of the partnership between the Andean country and the superpower, as it relates to combating drug trafficking.We work in the research with the concept of cooperation for policing, becausewe observe the operations carried out not only by the police agencies, but also those developed among the Armed Forces.We analyzedsome issues in the policingprocess, such as the expansion of actors involved in drug control and repression activities, their autonomy in the development of cooperation and the asymmetry of power between the bilateral relationship, which have helped our central objective. We concludedthat, unlike Bolivia-US cooperation, Brazil and Bolivia established, over the years 2008-2012, a bilateral cooperation for policing, with respect for territorial sovereignty and respect of each country's anti-drug policies